Introduction - Loboda, Egor L. (Journal of Physics: Conference Series)
The history of the All-Russian Scientific Conference “Conjugate Problem of Mechanics of Reactive Mediums, Informatics and Ecology” had started with scientific seminars, which began in 1973 at the initiative of young personnel of the Aerothermochemistry Department of the Research Institute of Applied Mathematics and Mechanics of Tomsk State University. They tested new scientific results and established channels with leading scientists of scientific schools.